Studi Analisis Pengaruh Perubahan Posisi Terhadap Efisiensi Panel Surya LPJU By Pass Ngurah Rai - Suantika, I Ketut; Rinas, Wayan; Suartika, I Made (Jurnal SPEKTRUM, 2018)
Utilization of sunlight as a source of renewable electrical energy by using photovoltaic (PV) has been done by many public and private agencies. One of them is Badung Regency Government. Power source for Main Street Lighting (LPJU) with the number of lamp posts 305 installed along the road By Pass I Gusti Ngurah Rai. This study analyzed the effect of position change on the efficiency of LPJU solar panel. The simulation of this research using PVSyst software and compared with real measurement result to get the position of solar cell that can produce optimal output power and better efficiency value. The result of comparison of rill measurement with PVSyst simulation, in zone 1 obtained maximum energy generation of 60,42 kWh, 186,40 kWh, at zone 2 equal to 72,54 kWh, 186,40 kWh, at zone 3 equal to 33,97 kWh, 186.40 kWh, in zone 4 of 61.52 kWh, 186.40 kWh. The PVSyst simulation results show that the solar cell output power is higher than the rear measurement in different directions and the efisiesin value obtained is better than the previous rill measurement.